Model Hujan Nonstasioner Dengan Variasi Waktu dan Tempat - Sutha Yadnya, Made; Mahmudah, Hani’ah (Transmisi, 2008)
In this paper the research about the making of nonstationary model mathematically of the channel communication influenced by rain condition is explained. The parameter of the model include the fading caused by polarization change of  30 GHz  milimeter-wave from LMDS (Local Multipoint Distribution Service). For supporting the parameters value there are three raingauges used in measuring the rainfall each in four measurement points at the campus area of  ITS (Institut Teknologi Surabaya).Key Words : Variasi Tempat, Variasi Waktu, LMDS